Evaluation of Chaotic Properties of CBC Mode of Encryption Embedded with RC5 Block Cipher Algorithm - Abidi, Abdessalem; Guyeux, Christophe; Machhout, Mohsen (Discontinuity, Nonlinearity, and Complexity, 2026)
It has been recently proven that, under ad hoc conditions, the Cipher Block Chaining (CBC) mode of operation can behave chaotically according to the mathematical definition of Devaney, on the infinite discrete product set of finite memory coupled with (finite) media of unbounded size. This occurs when the chosen block cipher function satisfies some properties related to a well defined associated graph. Rudimentary examples taken from so-called transposition cipher methods have formerly been proposed as illustrative examples. In this paper, the same canvas will be followed by regarding the conditions under which the CBC mode behaves chaotically. But the encryption function is now the Rivest Cipher 5 (RC5) one, a very famous symmetric key block cipher algorithm. Therefore, our goal is to prove the chaotic behavior of RC5-CBC encryption algorithm according to the reputed Devaney’s definition. Then, this unpredictability was checked in hardware through such sensitivity tests which allowed us to validate that RC5-CBC exhibits a high degree of randomness, key and plain sensitivity, in addition to the so-called avalanche effect.